Nestor Makhno and rural anarchism in Ukraine, 1917-21 - Darch, Colin (Pluto Press, 2020)
Reveals a little-known history of 1917: the Ukrainian anarcho-communist Makhnovists.
Keywords: Makhno, Nestor Ivanovich, -- 1889-1934.; Makhno, Nestor Ivanovich, -- 1889-1934; Anarchists -- Ukraine -- Biography.; Ukraine -- History -- Revolution, 1917-1921.; Anarchistes -- Ukraine -- Biographies.; Ukraine -- Histoire -- 1917-1921 (Révolution); HISTORY -- Revolutionary.; Anarchists; Ukraine; 1917-1921; Biography; Biographies; History; Biographies.